The Impact of Media Watching and Victim Gender on Victim and Offender Blameworthiness and Punishment - Schanz, Kimberley (Violence against women, 2024)
In recent years, there has been increased attention regarding the impact of the media on individuals’ perceptions of the criminal justice system, specifically focusing on the CSI effect and forensic evidence. In order to expand this area of research, this article focuses on the impact and interaction of crime-related media-watching habits and victim gender on perceptions of blameworthiness and punishment of both victims and aggressors in sexual assault cases. As expected, results supported the hypothesis that increased media-watching contributed to more stereotypical perceptions of sexual assault cases. However, slight variations observed in blameworthiness and punishment based on victim gender were nonsignificant. Implications for future research are discussed.